What Are the Financial Implications of Public Quality Disclosure? Evidence from New York City's Restaurant Food Safety Grading Policy. (January 2019) - Meltzer, Rachel; Rothbart, Michah W.; Schwartz, Amy Ellen; Calabrese, Thad; Silver, Diana; Mijanovich, Tod; Weinstein, Meryle
Grading schemes are an increasingly common method of quality disclosure for public services. Restaurant grading makes information about food safety practices more readily available and may reduce the prevalence of foodborne illnesses. However, it may also have meaningful financial repercussions. Using fine-grained administrative data that tracks food safety compliance and sales activity for the universe of graded restaurants in New York City and its bordering counties, we assess the aggregate financial effects from restaurant grading. Results indicate that the grading policy, after an initial period of adjustment, improves restaurants' food safety compliance and reduces fines. While the average effect on revenues for graded restaurants across the municipality is null, the graded restaurants located geographically closer to an ungraded regime experience slower growth in revenues. There is also evidence of revenue convergence across graded and ungraded restaurants in the long term.